Assessment of accredited veterinary diagnostic laboratory use of breakpoints for canine and feline Escherichia coli infections in the United States and Canada - Durr, Brandon J.; Ballard, Larry D.; Knight, Angela D.; Seo, Keun-Seok; Langston, Vernon C.; Thompson, Alexis C.; Shivley, Jacob M.; Brookshire, W. Cooper (Frontiers in Veterinary Science, 2023)
The objective of this study was to assess the use of breakpoints in antibiotic susceptibility testing among veterinary diagnostic laboratories in the United States and Canada. An eight-question survey was conducted via phone and email to determine how often laboratories use breakpoints consistent with published guidelines in wounds, lower urinary tract infections and upper urinary tract infections (pyelonephritis) involving E. coli, both in dogs and cats, for a total of 6 different hypothetical clinical scenarios. Nineteen veterinary diagnostic laboratories that perform antibiotic susceptibility testing on samples from dogs and cats in the US or Canada and were accredited by the American Association of Veterinary Laboratory Diagnosticians (AAVLD) responded to the survey between January 15th and September 15th, 2022. The overall response rate of laboratories that were not excluded for known lack of dog and cat antibiotic susceptibility testing was 19 of 44 laboratories. Of the 17 respondent laboratories that reported using minimal inhibitory concentration breakpoints, only four laboratories used breakpoints consistent with published guidelines in all six clinical scenarios included in the survey. Our results suggest that there is clinically important variation in what breakpoints laboratories use to determine antibiotic susceptibility, which is of antibiotic stewardship and clinical relevance. Using breakpoints that are too high, too low, or inappropriately reporting “not interpreted” as the interpretive category may result in inappropriate use of antibiotics.